PRIMING OF CHIKENS WITH LIVE AND INACTIVATED IBС VACCINE - Babak, V.A.; Gusev , A.A. (Eurasian Journal of Applied Biotechnology, 2023)
The research gives the results of the experiments to study the effect of priming the chickens with a live and inactivated vaccine against the IBC virus, and subsequent immunization with a live vaccine. The research demonstrates the results of the study of optimal schemes of birds’ immunization with live and inactivated vaccines, when the greatest specific effect is achieved. It has been established that priming chickens that do not contain antibodies against IBC with both live and inactivated vaccines causes the formation of intense immunity in them, which indicates a mature immune system capable of actively responding to a foreign antigen in the first days of life. Priming chickens with a live vaccine based on the background of maternal antibodies is not accompanied by the synthesis of antibodies, unlike priming with an inactivated vaccine, which leads to the formation of insignificant humoral immunity. Vaccination chickens containing maternal antibodies with live vaccine, primed with both live and inactivated vaccine depends on the content of specific antibodies in their body and is more effective when the level of antibodies in their body is low.